ANALYSIS OF THE EFFECTIVENESS OF COUNSELING AND POSTER TOWARDS ADHERENCE AND THERAPEUTIC OUTCOME ON HYPERTENSIVE PATIENTS - Risani Andalusia Putri; Retnosari Andrajati; Anton Bahtiar (Faculty of Pharmacy, Universitas Gadjah Mada)
Although the number of pharmacists in primary health care is limited, counseling is very important. The Government obligates primary health care to use poster as a health promotion method. In this study, counseling and poster were used to inform patients about hypertension and its therapy. The objective of this study was to compare the influence of counseling and poster towards adherence and therapeutic outcome on hypertensive patients in Bakti Jaya Primary Care, Depok. Research was conducted by quasi experimental using non-equivalent control group design. Samples were hypertensive patients at Bakti Jaya Public Health Care Depok collected from March to May 2012. Samples were divided into two groups i.e. counseling and poster groups. In the first group, pharmacist gave counseling to the patients and in the other group, the patients were only given poster. Patient’s adherence and blood pressure as therapeutic outcome were measured before (pre test) and after intervention (post test). Patient’s adherence was measured using Morisky Medication Adherence Scale (MMAS-8) questionnaire. This study showed that counseling enhanced adherence (P=0.000) and decreased systolic and diastolic blood pressure (P=0.010 and P=0.018), whereas poster only increased adherence (P=0.028). The differences of MMAS-8 score between counseling and poster group were significantly different (P=0.017), and the decreasing of systolic and diastolic blood pressure between counseling and poster group were not significantly different (P=0.170 and P=0.410).Keywords : Adherence, Hypertension, Counseling, Poster